Buddhism and modernity: sources from nineteenth-century Japan - Klautau, Orion; Krämer, Hans Martin (University of Hawaiʻi Press, 2021)
Questions and Answers from Beneath a Snowy Window (1876) by Fukuda Gyōkai / Micah Auerback -- On Religious Revolution (1889) by Nakanishi Ushirō / Hoshino Seiji -- Fraternity of Puritan Buddhists: Our Manifesto (1900) by Anonymous / Jolyon Baraka Thomas -- Discussing the Kanrenkai (1897) by Kyōkai Jigensha (attrib. Kiyozawa Manshi) / Jeff Schroeder -- On Protecting the Nation through Buddhism (1856) by Gesshō / Orion Klautau -- Upholding Faith in the Buddhadharma and Repaying the Nation (1863) by Ogawa Taidō / Jacqueline I. Stone -- Lectures on the Three Articles of Instruction (1873) by Higuchi Ryūon / Hans Martin Krämer -- Laughing at Christianity (1869) by Kiyū Dōjin / James Baskind -- On the National Doctrine of Greater Japan (1882) by Shaku Unshō / Kameyama Mitsuhiro and Nathaniel Gallant -- A Buddhist Book of Genesis (1879) by Sada Kaiseki / Fabio Rambelli -- The Gist of Indian Philosophy (1887) by Hara Tanzan / Dylan Luers Toda -- Prolegomena to an Argument for the Revival of Buddhism (1887) by Inoue Enryō / Jason Ā. Josephson-Storm -- Discourse on Buddhist Unity (1901) by Murakami Senshō / Ryan Ward -- On Civilization (1876) by Ōuchi Seiran / Orion Klautau -- Publishing Goals of Hanseikai zasshi (1887) and Living the Pure Life (1887) by Hanseikai zasshi / James Mark Shields -- On the Relationship Between Man and Woman (1888) by Shimaji Mokurai / Iwata Mami and Stephan Kigensan Licha -- On Buddhist Marriage (1894) by Tanaka Chigaku / G. Clinton Godart -- The Problem of Faith (1904) by Chikazumi Jōkan / Garrett L. Washington -- A Plan to Protect the Dharma (1874/1903) by Ogurusu Kōchō / Erik Schicketanz -- A Record of Niuzhuang (1895) by Yamagata Genjō / Micah Auerback -- The Japanese People's Spirit (1912) by Shaku Sōen / Michel Mohr -- A Travelogue in Tibet (1904) by Kawaguchi Ekai / Nathaniel Gallant
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Modernität; Buddhismus; Japan